STUDI PENURUNAN KONSENTRASI KROMIUM DAN SENG DALAM LIMBAH CAIR ELEKTROPLATING ARTIFICIAL DENGAN METODA ELEKTROKOAGULASI - Ryanti Christianna; Ganjar Samudro; Dwi Siwi Handayani (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
Electrocoagulation is selected method to decrease concentration of heavy metal Cr and Zn, because it is easy in operation without using chemical addition that harmful for human. The purpose of this research studied the influence of efficiency toward the loading of concentration and the performance of electrode during electrocoagulation process used on continuous system. This experiment used three types of artificial wastewater, they were waste 1 contained 30.11 mg/L of Cr, 50.61 mg/L of Zn, 50.14 mg/L of Cu, waste 2 contained 41.08 mg/L Cr, 105.30 mg/L Zn, 103.25 mg/L Cu, and waste 3 contained 50.07 mg/L of Cr, 202.58 mg/L of Zn, 208.61 mg/L of Cu. This experiment used aluminum electrode with dimension of 10 cm x 15 cm, voltage of 12 volt, current strength of 5 ampere, and the operating time was 360 minutes by taking sample every 30 minutes. There was the washing of electrode every 120 minutes to increase the performance of electrode. Based on the research had been obtained the optimum time at each sample was 120 minutes which research up to 97% of efficiency and the optimum time of using electrode was 240 minutes. The best reduction of Zn reached 97.68% with the initial concentration of 50.61mg/L.